The Integration of GPS Navigator Device with Vehicles Tracking System for Rental Cars Firms - Alharaki, Omarah Omar; Alaieri, Fahad Saleh; Zeki, Akram M. (LJS Publisher and IJCSIS Press, 2010)
The aim of this research is to integrate the GPS tracking system (tracking device and web-based application) with GPS navigator for rental cars, allowing the user to use various applications to monitor and manage the cars. This is enable the firms and customers to communicate with each other via the GPS navigator. The system should be developed by applying new features in GPS tracking application devices in vehicles. This paper also proposes new features that can be applied to the GPS Navigator. It also shows the benefits that the customers and staff will get from this system.